Left ventricular longitudinal contraction impacts the left atrial appendage function and the occurrence of thromboembolic events in patients with atrial fibrillation. (3rd October 2022) - Porca, A; Lazar, R D; Jelnean, M; Zehan, I G; Tentea, C P; Coseriu, G; Eotvos, C A; Andrei, M G; Givan, I; Pomian, A; Chiorescu, R; Rosianu, H; et al.
Abstract: Introduction: Previous research has revealed a relationship between left ventricular (LV) function and incidence of stroke in atrial fibrillation (AF) but the mechanism remains unknown. Purpose: Given that the left atrial appendage (LAA) is located in the vicinity of the LV base we hypothesized that the LV longitudinal contraction has an impact on the LAA function, LAA thrombus (LAAT) formation, and occurrence of ischemic stroke (Figure 1A). The aim of this study was to investigate this phenomenon using transesophageal echocardiography (TEE). Material and methods: We included in our study 105 consecutive patients (age 59±11; 55 men) undergoing TEE-guided cardioversion for AF. LV longitudinal function was assessed using the mitral annulus plane systolic excursion (MAPSE). LAA function was evaluated using the LAA emptying velocity (LAAEV) and LAA ejection fraction (LAAEF) (Figure 1B). The presence LAAT and spontaneous echo contrast (SEC) were evaluated as well. Results: Our patients had a median CHADS2vasc score = 3 (IQR 2–4), LVEF=50±11%, and MAPSE=7.3±1.7mm. MAPSE showed a positive significant correlation with both LAAEV (r=0.34; p<0.01) and LAAEF (r=0.23; p<0.05) (Figure 2). LVEF correlated significantly with LAAEV (r=0.42, p<0.01), and LAA area (r=−0.34; p<0.05), respectively. Additionally, patients who exhibited SEC had significantly lower LAAEF as well as LAAEV when compared with patients without SEC: 31±12% vs 38±12% P=0.022 and 35±18cm/s vs 49±21cm/s P=0.005. Patients who displayed both SEC and LAAT had wider LAA neck when compared to the rest of the group (21.46±3.96mm vs. 18.23±3.78mm; P=0.021). Logistic regression analysis revealed that MAPSE independently predicted the occurrence of ischemic stroke both in univariate and multivariate models that also included the CHADSvasc2 score. Conclusions: LV longitudinal contraction appears to influence LAA function. This relationship could potentially have an impact on occurrence of thromboembolic events in patients with atrial fibrillation. Funding Acknowledgement: Type of funding sources: None.